2020
DOI: 10.1089/jwh.2019.7732
|View full text |Cite
|
Sign up to set email alerts
|

Is Academic Medicine Making Mid-Career Women Physicians Invisible?

Abstract: In this perspective piece, we describe a multifactorial phenomenon whereby academic women physicians become invisible in the mid-career stage. Barriers, both small and large, cause a cumulative inequity effect, and women may leave academic medicine. Certainly, family and lifestyle choices play a role. And as we describe, so is a situation created where women become discouraged and disillusioned. We describe the growing evidence of subtle disparities, or micro-inequities, that cause women to be less visible and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(125 citation statements)
references
References 41 publications
3
101
0
1
Order By: Relevance
“…While studies have comprehensively investigated benefits and disadvantages of participating in citizenship tasks for work, 4,[6][7][8] few have explored how demographic factors impact self-perception and citizenship task load, especially among women physicians. [18][19][20][21][22] Our study highlights similar work found in the nonmedical literature as it pertains to gender and citizenship work tasks. 14,16,17,19,21,22 We found that the majority (67.0%) of women physicians reported spending between 1 and 5 hours weekly on work-related citizenship tasks and that nearly 50.0% of the women physicians surveyed reported a perception that they do more work-related citizenship tasks than their male colleagues.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While studies have comprehensively investigated benefits and disadvantages of participating in citizenship tasks for work, 4,[6][7][8] few have explored how demographic factors impact self-perception and citizenship task load, especially among women physicians. [18][19][20][21][22] Our study highlights similar work found in the nonmedical literature as it pertains to gender and citizenship work tasks. 14,16,17,19,21,22 We found that the majority (67.0%) of women physicians reported spending between 1 and 5 hours weekly on work-related citizenship tasks and that nearly 50.0% of the women physicians surveyed reported a perception that they do more work-related citizenship tasks than their male colleagues.…”
Section: Discussionsupporting
confidence: 77%
“…For example, literature has shown that men are rewarded for their altruistic work tasks, while women are expected, not rewarded, to enroll in similar activities. 1,2,9 A recent focus on the culture and climate of the workplace, [10][11][12][13] together with reports documenting slow progress in closing many gaps for people underrepresented in medicine (URiM), [14][15][16][17] inclusive of women in medicine, [18][19][20][21][22] has led us to consider the role that citizenship tasks may play. For example, although asking someone to take notes during a meeting that they are already attending may seem like a benign request, even small tasks may promote gender bias and expectations if a supervisor tends to ask primarily women who attend the meeting to record and disseminate minutes.…”
mentioning
confidence: 99%
“…Mid-career seems to be a particularly vulnerable time for female physicians. 17 , 28 , 29 , 30 Additionally, the notable decline in women who rise to higher ranks of leadership and seniority in EM 28 , 31 could be either a contributor to, or a result of, potentially higher burnout rates for women.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Por otra parte se encontró que la fuerza laboral femenina reporta menor edad que su contraparte masculina y se encuentra en su mayoría casadas y con al menos 1 hijo a diferencia de décadas anteriores 4 ; con poca frecuencia toman tiempo libre antes del parto y toman menor licencia de maternidad. 6,12,17,18 La producción científica en países desarrollados da cuenta de la mayor cantidad de manuscritos en relación con el tema de estudio, sin embargo la producción científica es liderada por hombres 21 Los países con menor grado de desarrollo socioeconómico muestran en forma objetiva, que el tema de inclusión femenina en fuerza laboral no es una de sus prioridades actualmente. El principal investigador del tema fuerza laboral encontrado en el análisis, corresponde a un hombre de Estados Unidos, lo que genera algo de preocupación al no tratarse de alguien del mismo género.…”
Section: Discussionunclassified